2010
DOI: 10.1123/japa.18.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Walkability: Older People’s Perspectives From Four Neighborhoods in Ottawa, Canada

Abstract: This qualitative study examined older people’s walking experiences in 4 Ottawa neighborhoods. Seventy-five adults age 65 years and older who had lived in their neighborhoods for at least 2 yr participated in focus groups and individual interviews. Four themes were identified through data analysis: multidimensional personal meanings, navigating hostile walking environments, experiencing ambiguity, and getting around. Neighborhood walking was experienced within the continuum of personal and environmental change.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 28 publications
6
46
0
Order By: Relevance
“…Environments with well-maintained streets, gardens and houses received higher invitingness-scores than environments that were less maintained. This is in concordance with previous qualitative research (Gallagher, et al, 2010;Grant, et al, 2010;Lees, et al, 2007) and a study by Borst et al (2009), who reported a negative relationship between the presence of litter and use of a street for transportation walking. Upkeep might not only influence walking for transportation by making places more aesthetically appealing, but also by influencing feelings of safety (Foster & Giles-Corti, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Environments with well-maintained streets, gardens and houses received higher invitingness-scores than environments that were less maintained. This is in concordance with previous qualitative research (Gallagher, et al, 2010;Grant, et al, 2010;Lees, et al, 2007) and a study by Borst et al (2009), who reported a negative relationship between the presence of litter and use of a street for transportation walking. Upkeep might not only influence walking for transportation by making places more aesthetically appealing, but also by influencing feelings of safety (Foster & Giles-Corti, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…by a curb, distance or physical barrier) were not associated with a higher invitingness. The importance of a clear separation between sidewalk and cycling path has been reported in qualitative studies (Grant, et al, 2010;. Possibly, this is more relevant for older adults with functional limitations as they might feel less capable of avoiding collisions with approaching cyclists and might be more fearful from falling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neighbourhood physical environmental features, characteristics and amenities such as safety and supportive features (e.g., wellmaintained pedestrian infrastructure, adequate benches, street lights), low traffic volume and flow, adequate public transportation (e.g., transit routes, physical design of bus stops), enjoyable scenery, can play a role in supporting the mobility of older residents in their neighbourhood (Cauwenberg et al, 2011;Glass and Balfour, 2003;Grant et al, 2010b;Michael et al, 2011;Rosenberg et al, 2013;. Accordingly, a supportive neighbourhood physical environment is likely to facilitate opportunities to be physically active and socially engaged (e.g., Chaudhury et al, 2012Chaudhury et al, , 2011Mahmood et al, 2012;Nagel et al, 2008;Phillips et al, 2005;Rosenberg et al, 2012;Yen and Anderson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Composite indices are then computed over areas at the granularity of neighbourhoods or census blocks (Leslie et al 2007;Weiss, Maantay and Fahs 2010;Freeman et al 2012;Giles-Corti et al, 2014;Buck and Tkaczick 2014). However, the actual relation between those variables and walkability is not uncontested (Grant et al 2010 and references therein). On a more functional level, walkability is quantified using data that is generally surveyed specifically to suit this purpose using audit forms, e.g.…”
Section: Walkabilitymentioning
confidence: 99%